Regional Anesthesia Strategy Using Thoracic Paravertebral Block in a Patient with Tuberculosis-Related Pyopneumothorax: A Case Report - T Arfi Sulaiman; Rahendra Rahendra (Journal of Society Medicine, 2026)
Thoracic surgery in patients with severe pulmonary disease poses significant anesthetic challenges. General anesthesia with positive pressure ventilation may exacerbate ventilation–perfusion mismatch and worsen air leakage in the presence of a bronchopleural fistula. Regional anesthesia techniques that preserve spontaneous ventilation may offer a safer alternative in selected high-risk patients. We report a case of a 68-year-old male with tuberculosis-related right-sided pyopneumothorax complicated by bronchopleural fistula, severe chronic obstructive pulmonary disease with a restrictive component, atrial fibrillation with normal ventricular response, and hepatic insufficiency (ASA physical status III), who was scheduled for an open pleural window procedure. Given the high risk of general anesthesia and mechanical ventilation, ultrasound-guided unilateral thoracic paravertebral block (TPVB) was selected as the primary anesthetic technique, combined with dexmedetomidine sedation. The block was performed at T5–T7 using ropivacaine, achieving adequate dermatomal anesthesia. Sedation was titrated to preserve spontaneous ventilation and patient cooperation. The procedure was completed without conversion to general anesthesia. The patient remained hemodynamically stable, with preserved spontaneous breathing and adequate oxygenation throughout the surgery. No vasopressors, rescue opioids, or airway interventions were required. Postoperative pain was minimal, and no block-related or respiratory complications occurred. Thoracic paravertebral block combined with dexmedetomidine sedation provided effective anesthesia and favorable perioperative stability for open pleural window surgery in a high-risk pulmonary patient. This case highlights the potential role of regional anesthesia-based strategies as an alternative to general anesthesia in carefully selected thoracic surgical patients where preservation of spontaneous ventilation is desirable.